Formulasi Pil Kunyit (Curcuma Longa L.) Kombinasi Sari Jeruk Limau Kuit (Citrus Hystrix Dc.) Sebagai Antioksidan - Shesanthi Citrariana; Muhammad Priyadi; Defilia Anograh R; Sudarman Rahmman; Yahya Febrianto; Ahmad Irawan; Franz June N; Shavira Elphasa H; Allaya Adistia P (Sinteza, 2026)
Turmeric contains the active compound curcumin, which has been studied for its various biological activities, including antioxidant, anti-inflammatory, antimicrobial, and immunomodulatory properties. Kaffir lime is a plant commonly found on the island of Borneo and is used in traditional medicine and culinary flavors. Kaffir lime fruit and leaves contain various bioactive compounds, such as flavonoids (hesperidin, naringenin), essential oils (citronellal, limonene), and vitamin C. Flavonoids are known to have antioxidant and anti-inflammatory effects that can boost the immune system. Pills are one of the oldest dosage forms in the pharmaceutical world and are still relevant, especially for herbal preparations due to their ease of manufacture and stability. This study aims to formulate pill preparations by combining turmeric and lime juice. The method used is wet granulation to make pills with varying turmeric concentrations, namely F1 0.26% and F2 0.52% using polyvinyl alcohol as a binder. Physical evaluations include water content, weight uniformity, pH, and disintegration time tests. The pills were then tested for antioxidant activity against DPPH. The results showed that the water content of F1 pills was 4.06% and F2 pills 3.75%, pill weight uniformity with RSD value criteria of F1 was 0.21% and F2 pills 3.40%, the average pH of F1 was 6.32 and F2 pills 6.22, and the disintegration time of F1 was 30 minutes and F2 pills 8.26 minutes. The results of the antioxidant activity of the pill preparations showed that the F1 IC50 was 6.36 ppm and the F2 IC50 was 5.53 ppm. From the results obtained, it can be concluded that F2 pill preparations have good physical properties and potential antioxidant activity.